Crime in England 1880-1945 the rough and the criminal, policed and the incarcerated - Godfrey, Barry S. (London Routledge/Taylor & Francis Group, 2014)
"this book is an ambitious attempt to map the main changes in the criminal justice system in the Victorian period through to the twentieth century. Chapters include an examination of the growth and experience of imprisonment, policing, and probation services; the recording of crime in official statistics and in public memory; the possibilities of research created by new electronic and online resources; an exploration of time, space and place, on crime; and the growth of internationalisation and science-led approach of crime control methods in this period."--Back cover.
Includes bibliographical references and index.
Keywords: Crime -- History -- 19th century. -- Great Britain; Crime -- History -- 20th century. -- Great Britain; Criminal justice, Administration of -- History. -- Great Britain; Police -- History. -- Great Britain